Experience of Caregiver Coping Mechanisms When Taking Care of a Schizophrenic Patient - Rindayati,; Yusuf, Ah; Efendi, Ferry; Illahiati, Nisa Kurnia; Nasir, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to discuss the experience of protected caregivers when treating schizophrenic patients. Coping strategies are the strategy used to overcome stressors. The use of a coping strategy can be either destructive or constructive. Caregivers must undergo coping in order to care for schizophrenic patient to overcome the stress. This research used an interpretive phenomenology paradigm. The samples were selected using purposive sampling totaling 7 people with experience of caring for at least 1 year, who were physically and psychologically healthy, who were accepted as a participant and who could describe their coping mechanism experience well. The research instrument was the researcher. The data collected was through in-depth interviews and observations. The results of the interviews were analyzed using the Van Manen (1990) method to maintain the authenticity of the life experiences or phenomena while investigating the existing experiences based on the phenomena, reflecting on the essential themes that characterize the phenomena and describing and correcting phenomena. The researcher obtained 5 themes from the data, namely the effect as a stressor, the effect of stressors on feelings, actions in caring, changes during treatment, and coping strategies. The use of coping strategies by the caregivers is a way of coping that focuses on problems and coping that focuses on emotions. Based on the results of the study, it is expected that caregivers will go on to use fully adaptive coping when treating schizophrenic patients at home. The use of adaptive coping strategy resulted in the patient care being optimally supported.